Process for the preparation of low resistance ohmic contacts for high voltage devices
Patent Information
- Application Number
- CN202611172159.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
然而,上述方法中,离子注入会在半导体表面引入晶格损伤层,若退火激活不充分,损伤将部分残留,导致载流子迁移率下降、接触电阻率波动较大;而若采用900℃以上甚至1000℃量级的高温退火,又易引起金属电极与半导体界面互扩散、金属团聚以及氧空位分布失控,造成接触形貌恶化、器件反向漏电增大,接触的热稳定性及大电流可靠性不足
[0025]1)本发明通过在β-Ga2O3肖特基二极管阴极接触区域采用Si+多能量组合离子注入方式,使Si元素在衬底表层形成梯度分布的掺杂区域,提高阴极接触区域载流子浓度,减小金属与β-Ga2O3之间的界面耗尽层宽度,增强电子传输能力,从而降低欧姆接触电阻,提高器件导通性能;
Smart Images

Figure CN122892243A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor device manufacturing technology, and more specifically, relates to a process for preparing low-resistance ohmic contacts for high-voltage devices. Background Technology
[0002] With the development of power electronics technology towards high voltage, high current, and low loss, wide-bandgap and ultra-wide-bandgap semiconductor materials have attracted widespread attention in the field of power devices. β-Ga₂O₃, as a new generation of ultra-wide-bandgap semiconductor material, has a bandgap of approximately 4.8 eV to 4.9 eV and a theoretical breakdown field strength on the order of 8 MV / cm, giving it the material advantage of fabricating high-voltage, low-conduction-loss power devices. Furthermore, β-Ga₂O₃ can be grown into large-size single-crystal substrates using melt methods such as the EFG (Exposed-Electrical Mode Grafting) and Czochralski (CZ) methods, resulting in relatively low manufacturing costs. Therefore, it has significant application value in high-voltage rectification and power electronic conversion.
[0003] Due to the large bandgap of β-Ga₂O₃, the contact barrier formed between it and most metals is high, making it difficult to achieve an ideal low-barrier ohmic contact. Metal-semiconductor interfaces often exhibit strong Schottky characteristics rather than ideal ohmic characteristics. Furthermore, because β-Ga₂O₃ lacks effective p-type doping methods, its surface state density and oxygen vacancy distribution in the contact region are uneven. The natural oxide layer and surface damage layer further exacerbate the interface state pinning effect, leading to significant Fermi level pinning and high contact resistivity. Under conventional process conditions, the specific contact resistivity is typically around 10⁻⁶. -5 Ω·cm 2 ~10 -4 Ω·cm 2 The magnitude of the current is insufficient to meet the requirements of high-voltage, high-current devices for low conduction losses.
[0004] To reduce contact resistance, ion implantation of donor elements such as Si and Sn is performed in the β-Ga2O3 contact region to form a locally heavily doped layer, followed by deposition of metal stacks such as Ti / Au and Ti / Al / Ni / Au, and then high-temperature rapid thermal annealing. However, in the above method, ion implantation introduces a lattice damage layer on the semiconductor surface. If the annealing activation is insufficient, some damage will remain, leading to a decrease in carrier mobility and large fluctuations in contact resistivity. On the other hand, if high-temperature annealing of 900°C or even 1000°C is used, it is easy to cause interdiffusion between the metal electrode and the semiconductor interface, metal agglomeration, and uncontrolled oxygen vacancy distribution, resulting in deterioration of contact morphology, increased reverse leakage current of the device, and insufficient thermal stability and high-current reliability of the contact.
[0005] Furthermore, this method often employs a single metal or simple double-layer metal electrode structure, making it difficult to simultaneously achieve low contact work function matching, good adhesion, anti-electromigration capability, and compatibility with subsequent interconnect processes. Devices are prone to reliability issues such as electrode peeling and electromigration failure under long-term high-current operation. Moreover, existing processes lack precise control over the annealing atmosphere and heating rate, generally employing a single high-temperature annealing process. This makes it difficult to achieve synergistic optimization of damage repair and metal alloying reactions, resulting in poor uniformity of contact resistance and batch consistency.
[0006] Therefore, how to achieve low contact resistivity, high thermal stability, and high current reliability while ensuring low damage through the coordinated optimization of contact area surface state control, local high conductivity layer construction, composite metal electrode design, and annealing process is an urgent technical problem to be solved. Summary of the Invention
[0007] In view of the above-mentioned problems in the existing technology, the technical problem to be solved by the present invention is to provide a process for fabricating low-resistance ohmic contacts for high-voltage devices.
[0008] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0009] A process for fabricating a low-resistance ohmic contact for a high-voltage device includes the following steps:
[0010] 1) Provide a β-Ga2O3 single crystal substrate, and perform surface pretreatment on the β-Ga2O3 single crystal substrate to obtain the substrate surface to be formed with ohmic contacts;
[0011] 2) Using Si + The ohmic contact region of the β-Ga2O3 single crystal substrate is doped by ion implantation to form a Si doped layer in the ohmic contact region.
[0012] 3) Heat treatment was performed on the β-Ga2O3 single crystal substrate with Si doped layer to obtain doped and activated n-type conductive region;
[0013] 4) Ti layer, Ni layer, Al layer and Au layer are sequentially formed on the surface of the n-type conductive region obtained in step 3) to obtain a composite metal electrode;
[0014] 5) Perform alloying annealing on the β-Ga2O3 single crystal substrate with the composite metal electrode formed in step 4) to form an ohmic contact between the composite metal electrode and the n-type conductive region.
[0015] Preferably, in step 1), the β-Ga₂O₃ single crystal substrate is a Sn-doped β-Ga₂O₃ single crystal substrate, and the Sn doping concentration is 1×10⁻⁶. 18 ~5×10 18cm -3 .
[0016] Preferably, in step 1), the surface pretreatment process is as follows: the β-Ga2O3 single crystal substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence, then acid-treated with hydrochloric acid solution, dried with high-purity nitrogen gas, and activated with Ar plasma.
[0017] Preferably, the radio frequency power of the Ar plasma activation treatment is 30~50 W, the working pressure is 5~20 Pa, and the treatment time is 30~120 s.
[0018] Preferably, in step 2), the Si + Ion implantation employs a multi-energy combination implantation method, including: a first implantation energy of 30-40 keV; a second implantation energy of 70-80 keV; and a third implantation energy of 110-120 keV; the Si... + The total ion implantation dose was 5 × 10⁻⁶. 14 ~2×10 15 cm -2 .
[0019] Preferably, in step 2), Si + The thickness of the Si doped layer formed by ion implantation is 80~150 nm.
[0020] Preferably, in step 3), the heat treatment process is as follows: in the first stage, under a N2 protective atmosphere, the heat treatment is carried out at 400~500℃ for 10~30 min; in the second stage, under a N2 protective atmosphere, the heat treatment is carried out at 850~960℃ for 30~120 s.
[0021] Preferably, in step 4), the thickness of the Ti layer is 10~30 nm; the thickness of the Ni layer is 20~50 nm; the thickness of the Al layer is 100~400 nm; and the thickness of the Au layer is 50~100 nm.
[0022] Preferably, in step 5), the alloying annealing treatment is carried out under a N2 protective atmosphere, the annealing temperature is 400~500℃, and the annealing time is 1~5 min.
[0023] A low-resistance ohmic contact structure for a high-voltage device includes a β-Ga2O3 single-crystal substrate, a Si-doped n-type conductive layer disposed on the surface of the β-Ga2O3 single-crystal substrate, and a Ti / Ni / Al / Au composite metal electrode disposed on the surface of the Si-doped n-type conductive layer; wherein the Si-doped n-type conductive layer and the Ti / Ni / Al / Au composite metal electrode form an ohmic contact.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0025] 1) This invention employs Si in the cathode contact region of a β-Ga2O3 Schottky diode. + The multi-energy combined ion implantation method enables Si elements to form a gradient distribution doped region on the substrate surface, which increases the carrier concentration in the cathode contact region, reduces the width of the depletion layer at the interface between the metal and β-Ga2O3, enhances electron transport capability, thereby reducing ohmic contact resistance and improving device conduction performance.
[0026] 2) This invention employs a graded heat treatment process that combines low-temperature pre-annealing with rapid thermal annealing. This process alleviates lattice damage caused by ion implantation while promoting the electroactivation of Si dopants, resulting in a high-concentration n-type conductive region with good crystal quality and electrical properties. This avoids the problem of increased defects or insufficient doping activation caused by a single high-temperature annealing.
[0027] 3) This invention improves the problem of difficult cathode ohmic contact caused by the wide bandgap characteristics of β-Ga2O3 material through the synergistic effect of surface activation treatment, multi-energy gradient doping, hierarchical thermal activation and composite metal regulation, so that the prepared cathode ohmic contact structure has low contact resistance, good current transmission capability and high thermal stability.
[0028] 4) The preparation method of this invention is compatible with existing semiconductor manufacturing processes. It can be achieved by combining ion implantation, heat treatment and metal deposition processes. No complex equipment or special materials are required. It is suitable for the preparation of wide bandgap semiconductor power devices such as β-Ga2O3 Schottky diodes. Attached Figure Description
[0029] Figure 1 A comparison of the ohmic contact ratio and contact resistivity of different β-Ga2O3 cathode samples;
[0030] Figure 2 A comparison of current densities of different cathode ohmic contacts under a 5 V bias voltage;
[0031] Figure 3 The change rate of contact resistance of different samples after thermal aging at 300℃ for 100 h. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention is further described below with reference to specific embodiments. Unless otherwise specified, the technical means used in the following embodiments are all conventional means well known to those skilled in the art. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0033] Example 1
[0034] This embodiment provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0035] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0036] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 40 keV, the second implantation energy was 80 keV, and the third implantation energy was 120 keV, with a total implantation dose of 1 × 10⁻⁶. 15 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0037] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 500℃ for 20 min, then use a rapid thermal annealing process to process at 900℃ for 60 s to form a low-resistance n-type conductive contact region.
[0038] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm.
[0039] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0040] Example 2
[0041] This embodiment provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0042] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0043] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 40 keV, the second implantation energy was 80 keV, and the third implantation energy was 120 keV, with a total implantation dose of 8 × 10⁻⁶. 14 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0044] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 500℃ for 20 min, then use a rapid thermal annealing process to process at 900℃ for 60 s to form a low-resistance n-type conductive contact region.
[0045] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm.
[0046] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0047] Example 3
[0048] This embodiment provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0049] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0050] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 30 keV, the second implantation energy was 70 keV, and the third implantation energy was 110 keV, with a total implantation dose of 1 × 10⁻⁶. 15 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0051] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 500℃ for 20 min, then use a rapid thermal annealing process to process at 900℃ for 60 s to form a low-resistance n-type conductive contact region.
[0052] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm.
[0053] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0054] Example 4
[0055] This embodiment provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0056] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0057] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 40 keV, the second implantation energy was 80 keV, and the third implantation energy was 120 keV, with a total implantation dose of 1 × 10⁻⁶. 15 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0058] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 450℃ for 20 min, then use a rapid thermal annealing process to process at 960℃ for 60 s to form a low-resistance n-type conductive contact region.
[0059] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm.
[0060] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0061] Example 5
[0062] This embodiment provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0063] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0064] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 40 keV, the second implantation energy was 80 keV, and the third implantation energy was 120 keV, with a total implantation dose of 1 × 10⁻⁶. 15 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0065] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 500℃ for 20 min, then use a rapid thermal annealing process to process at 900℃ for 60 s to form a low-resistance n-type conductive contact region.
[0066] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 15 nm, the thickness of Ni is 40 nm, the thickness of Al is 250 nm, and the thickness of Au is 80 nm.
[0067] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0068] Comparative Example 1
[0069] This comparative example provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0070] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0071] 2) The substrate from step 1) was subjected to graded annealing in a nitrogen protective atmosphere: first, it was pre-annealed at 500°C for 20 min, and then a rapid thermal annealing process was used to process it at 900°C for 60 s to form a low-resistance n-type conductive contact area.
[0072] 3) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 2), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm;
[0073] 4) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0074] Comparative Example 2
[0075] This comparative example provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0076] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0077] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was single-energy implantation: the implantation energy was 120 keV and the implantation dose was 1 × 10⁻⁶. 15 cm-2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by single-energy injection;
[0078] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 500℃ for 20 min, then use a rapid thermal annealing process to process at 900℃ for 60 s to form a low-resistance n-type conductive contact region.
[0079] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm.
[0080] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0081] Comparative Example 3
[0082] This comparative example provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0083] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0084] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 40 keV, the second implantation energy was 80 keV, and the third implantation energy was 120 keV, with a total implantation dose of 1 × 10⁻⁶. 15 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0085] 3) After ion implantation in step 2), the substrate is placed in a nitrogen protective atmosphere and annealed at 900°C for 60 seconds to form a low-resistance n-type conductive contact region.
[0086] 4) Using the electron beam evaporation method, a Ti / Ni / Al / Au composite metal layer is sequentially deposited in the n-type conductive contact region in step 3), wherein: the thickness of Ti is 20 nm, the thickness of Ni is 30 nm, the thickness of Al is 200 nm, and the thickness of Au is 80 nm.
[0087] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0088] Comparative Example 4
[0089] This comparative example provides a method for preparing a β-Ga2O3 Schottky diode cathode ohmic contact, including the following steps:
[0090] 1) A Sn-doped β-Ga2O3 single crystal substrate was selected as the device substrate. The substrate has a (-201) crystal plane and a Sn doping concentration of 3 × 10⁻⁶. 18 cm -3 The substrate was ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each to remove surface organic contaminants. It was then treated in a 5% hydrochloric acid solution for 60 seconds to remove adsorbed impurities and weakly bound oxide residues. After rinsing with deionized water, it was dried with high-purity nitrogen. Finally, Ar plasma was used to activate the cathode contact area at a radio frequency power of 40 W, a working pressure of 10 Pa, and a treatment time of 60 seconds.
[0091] 2) On the substrate treated in step 1), Si is used + Ion implantation was used to perform shallow doping on the cathode contact region. The implantation scheme was a three-stage multi-energy implantation: the first implantation energy was 40 keV, the second implantation energy was 80 keV, and the third implantation energy was 120 keV, with a total implantation dose of 1 × 10⁻⁶. 15 cm -2 A gradient-distributed Si-doped region is formed on the surface of β-Ga2O3 by multi-energy injection;
[0092] 3) Place the substrate after ion implantation in step 2) under a nitrogen protective atmosphere for graded annealing: first, pre-anneal at 500℃ for 20 min, then use a rapid thermal annealing process to process at 900℃ for 60 s to form a low-resistance n-type conductive contact region.
[0093] 4) Using electron beam evaporation, a Ti / Au composite metal layer is sequentially deposited in the n-type conductive contact region of step 3), wherein the thickness of Ti is 20 nm and the thickness of Au is 80 nm;
[0094] 5) After deposition, the device is placed in a nitrogen protective atmosphere for rapid thermal annealing at a temperature of 450°C for 3 minutes to form a stable ohmic contact interface between the metal layer and β-Ga2O3, resulting in a low contact resistance cathode structure.
[0095] The devices prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests, and the test methods are as follows:
[0096] 1. Specific contact resistivity test
[0097] The performance of the β-Ga2O3 cathode ohmic contact was tested using the Transmission Line Model (TLM) method. The specific method is as follows: test electrodes with different spacings were fabricated on the surface of the prepared β-Ga2O3 ohmic contact structure. The resistance values at different electrode spacings were measured using a semiconductor parameter analyzer, and the specific contact resistivity was calculated based on the resistance-spacing relationship curve. Test conditions: The test temperature was room temperature (25℃), and the current scan range was -10 mA to 10 mA.
[0098] 2. Current-Voltage (IV) Characteristic Test
[0099] The current-voltage characteristics of the cathode ohmic contact region of the device were tested using a semiconductor parameter analyzer. Test conditions: test temperature 25℃, scan voltage range -5 to 5 V, scan rate 0.05 V / s. The conductivity of the ohmic contact was evaluated by the slope of the linear region.
[0100] 3. High-temperature thermal stability test
[0101] The prepared ohmic contact structure was subjected to thermal aging tests in a nitrogen-protected environment. Test conditions: aging temperature 300℃, aging time 100 h; the change rate of specific contact resistivity before and after aging was measured to evaluate the thermal stability of the metal / semiconductor interface. The test results are shown in Table 1.
[0102] Table 1 Performance test results of different samples
[0103]
[0104] As shown in Table 1, this invention utilizes surface activation and multi-energy Si... +The synergistic effect of gradient implantation, graded thermal activation annealing, and Ti / Ni / Al / Au composite metal electrodes enables the β-Ga2O3 Schottky diode cathode ohmic contact to simultaneously achieve low specific contact resistivity, high electron transport capability, and excellent thermal stability. In Example 1, compared to the example without Si... + The injected comparative example 1 showed a reduction of approximately 85% in contact resistivity and approximately 86% in thermal aging resistance change rate, indicating that the technical solution of the present invention can effectively solve the problems of high cathode ohmic contact resistance and insufficient interface stability in existing β-Ga2O3 devices, and has good application value.
[0105] Depend on Figure 1 It can be seen that the ohmic contact structures prepared in Examples 1-5 have significantly reduced specific contact resistivity, with Example 1 having the lowest resistivity at only 8.2 × 10⁻⁶. -6 Ω·cm 2 In contrast, Comparative Examples 1-4 lack Si, respectively. + Gradient implantation, gradient doping structures, graded annealing processes, or composite metal modulation all significantly increase the specific contact resistivity, indicating that the multi-energy Si used in this invention... + Injection, hierarchical thermal activation, and Ti / Ni / Al / Au composite metal structures can effectively reduce the metal / β-Ga2O3 interface barrier and improve carrier transport capability.
[0106] Depend on Figure 2 It can be seen that the samples in Examples 1-5 all exhibited high current transport capability, with Example 1 reaching a current density of 1520 A / cm² under a 5 V bias voltage. 2 The value was significantly higher than that of the other pairs. This indicates that by forming a shallow, high-concentration n-type contact region and optimizing the metal / semiconductor interface structure, the electron injection impedance can be effectively reduced and the device conductivity improved.
[0107] Depend on Figure 3 It can be seen that after thermal aging at 300℃ for 100 h, the contact resistance change rate of samples in Examples 1-5 was all less than 18%, with Example 1 showing only 7.3%, demonstrating excellent thermal stability. In contrast, the comparative samples, due to insufficient interface control, exhibited a significantly increased resistance change rate, especially Comparative Example 4, which, using a traditional Ti / Au electrode structure, reached a change rate of 65.1%. This indicates that the composite metal structure of the present invention can effectively suppress interface diffusion and performance degradation under high-temperature conditions, improving the long-term reliability of the device.
[0108] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A process for fabricating a low-resistance ohmic contact for a high-voltage device, characterized in that, Includes the following steps: 1) Provide a β-Ga2O3 single crystal substrate, and perform surface pretreatment on the β-Ga2O3 single crystal substrate to obtain the substrate surface to be formed with ohmic contacts; 2) Using Si + The ohmic contact region of the β-Ga2O3 single crystal substrate is doped by ion implantation to form a Si doped layer in the ohmic contact region. 3) Heat treatment was performed on the β-Ga2O3 single crystal substrate with Si doped layer to obtain doped and activated n-type conductive region; 4) Ti layer, Ni layer, Al layer and Au layer are sequentially formed on the surface of the n-type conductive region obtained in step 3) to obtain a composite metal electrode; 5) Perform alloying annealing on the β-Ga2O3 single crystal substrate with the composite metal electrode formed in step 4) to form an ohmic contact between the composite metal electrode and the n-type conductive region.
2. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 1), the β-Ga₂O₃ single crystal substrate is a Sn-doped β-Ga₂O₃ single crystal substrate, and the Sn doping concentration is 1×10⁻⁶. 18 ~5×10 18 cm -3 .
3. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 1), the surface pretreatment process is as follows: the β-Ga2O3 single crystal substrate is ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence, then acid-treated with hydrochloric acid solution, dried with high-purity nitrogen gas, and activated with Ar plasma.
4. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 3, characterized in that, The radio frequency power of the Ar plasma activation treatment is 30~50 W, the working gas pressure is 5~20 Pa, and the treatment time is 30~120 s.
5. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 2), the Si + Ion implantation employs a multi-energy combination implantation method, including: a first implantation energy of 30-40 keV; a second implantation energy of 70-80 keV; and a third implantation energy of 110-120 keV; the Si... + The total ion implantation dose was 5 × 10⁻⁶. 14 ~2×10 15 cm -2 .
6. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 2), Si + The thickness of the Si doped layer formed by ion implantation is 80~150 nm.
7. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 3), the heat treatment process is as follows: in the first stage, under a N2 protective atmosphere, the heat treatment is carried out at 400~500℃ for 10~30 min; in the second stage, under a N2 protective atmosphere, the heat treatment is carried out at 850~960℃ for 30~120 s.
8. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 4), the thickness of the Ti layer is 10~30 nm; the thickness of the Ni layer is 20~50 nm; the thickness of the Al layer is 100~400 nm; and the thickness of the Au layer is 50~100 nm.
9. The fabrication process for low-resistance ohmic contacts in high-voltage devices according to claim 1, characterized in that, In step 5), the alloying annealing treatment is carried out under a N2 protective atmosphere, the annealing temperature is 400~500℃, and the annealing time is 1~5 min.
10. A low-resistance ohmic contact structure for a high-voltage device, characterized in that, The device includes a β-Ga2O3 single crystal substrate, a Si-doped n-type conductive layer disposed on the surface of the β-Ga2O3 single crystal substrate, and a Ti / Ni / Al / Au composite metal electrode disposed on the surface of the Si-doped n-type conductive layer; wherein the Si-doped n-type conductive layer and the Ti / Ni / Al / Au composite metal electrode form an ohmic contact.